Fatores associados à estrutura da comunidade de liquens corticícolas crostosos em duas áreas de caatinga no estado de Alagoas - Cavalcante, Janice Gomes (2012)
About one fifth of the fungi are found in nature in symbiosis with algae and / or cyanobacteria, most of these fungi members of the Phylum Ascomycota, with only a few representatives of Basidiomycota which are lichenized. This association, considered a very successful nutritional strategy, is called lichenization, and the structure formed in this process, lichen. In this stable biological unit, the fungus is the mycobiont and photosynthetic organisms are photobionts. The Caatinga biome is an endemic Brazilian semiarid region, dominated by vegetation types with xerophytic characteristics and extracts composed of grasses, shrubs and trees. In the State of Alagoas, the Caatinga occupies an area of ca. 16.350km2 and in spite of extreme temperature and low amount of rainfall, it comprises important lichen groups not yet properly studied in the State. This study was conducted in two areas in the hinterland of Caatinga in Alagoas State, located in the municipality of Santana do Ipanema. The first area is the R.P.P.N. Farm Waterfall in Serra da Tocaia, and the second is a disturbed area, located 10 km from the city limits, in the Serra do Gugi. The results of this study are divided into two chapters. The first relates lichens groups registered in the study areas, where samples were collected from 60 phorophytes hosts also relates ecological data such as elevation, diameter at breast height and pH of the bark. A total of 61 taxa were identified, distributed in 18 families and 34 genera. Of these, one species ise new to science; 08 represent new records for Latin America, 10 for Brazil, 04 for the Northeast Region and 49 are new to the State of Alagoas. The second chapter presents the description of a new species to science, Opegrapha caeruleohymeniata JG Cavalcante, Aptroot & M. Cáceres. The pioneering aspect of this work and the data obtained point to the need for further studies in the region, which was showed to be lichen rich and unexplored. Moreover, it represents a significant contribution to the field of lichenology in the region and in the country.